2016
DOI: 10.3906/vet-1507-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of antioxidant retinol, melatonin, and zinc during in vitro maturation of bovine oocytes under induced heat stress

Abstract: Both A and B grade cumulus-oocyte complexes (COCs) aspirated from cattle ovaries at slaughter were matured in vitro under normal (38.5 °C) and elevated temperatures (41 °C). Maturation competence based on cumulus expansion, COC diameter, and nuclear maturation were compared with and without antioxidant supplementation incorporating 7.5 µM retinol, 1 nM melatonin, and 1.5 µg/mL zinc chloride in an oocyte maturation medium. Heat stress significantly reduced cumulus expansion by approximately 20%, while only reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The concentration of melatonin used here, 1 µM, is much higher than the reported kD of membrane melatonin receptors, having values of ~30−225 pM (Poon et al , 1994; Kobayashi et al , 2003; Liu et al , 2013). In an earlier study, there was no thermoprotective effect of 1 pM or 1 nM melatonin on bovine oocytes exposed to heat shock (Cebrian-Serrano et al , 2013; Ahmed et al , 2016).…”
Section: Discussionmentioning
confidence: 89%
“…The concentration of melatonin used here, 1 µM, is much higher than the reported kD of membrane melatonin receptors, having values of ~30−225 pM (Poon et al , 1994; Kobayashi et al , 2003; Liu et al , 2013). In an earlier study, there was no thermoprotective effect of 1 pM or 1 nM melatonin on bovine oocytes exposed to heat shock (Cebrian-Serrano et al , 2013; Ahmed et al , 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, Cajuday et al [5] postulated that adding RA (1 or 5 nM) to the maturation media of buffalo oocytes improved the cleavage rate. Under elevated temperature (41 °C for the first 12 h and 38.5 °C for the second 12 h), RA supplementation at the 7.55 nM level to in vitro embryo production exhibited highly significant ( p < 0.01) cleavage rates compared to controls (38.5 °C for 24 h) in bovine species [40]. Conversely, Islam et al [41] state that RA (5 nM) supplemented to the in vitro bovine oocyte maturation medium did not influence the cleavage rates.…”
Section: Effects Of Ra and Retinol On Oocyte Until Blastocyst Formmentioning
confidence: 99%
“…Moreover, Hidalgo et al [44] indicated that the in vitro maturation of bovine oocytes in the presence of 9-cisRA (5 nM) resulted in higher oocyte competence, blastocyst formation and hatching rate, pregnancy rate, and cell count and proportion of cells in the inner mass of day seven blastocysts. Moreover, the supplementation of 7.55 nM RA to bovine oocytes under elevated temperature (41 °C) significantly improved the embryonic stages (2–4 cells, 8–16 cells, morula, and blastocyst) compared to those in the control group [40]. This enhancement of embryonic stages under thermal stress reflects the potential function of RA forms for overcoming the deleterious effects of elevated temperature.…”
Section: Effects Of Ra and Retinol On Oocyte Until Blastocyst Formmentioning
confidence: 99%
“…The sensitivity of pre-implantation embryos to different stress conditions (oxidation, toxicity and hypothermia) causes various types of embryo damage, in terms of mitochondrial and lysosomal changes as well as accumulation of lipid droplets (Olexikova et al, 2013). During heat shock, free radical production had been suspected leading to promote oxidation events in the cell (Ara Ahmed et al, 2016). In vivo or in vitro heat stress caused a decrease in GSH of embryos, and elevated ROS levels associated with DNA damage in mice (Ozawa et al, 2002).…”
Section: Effect Of Interactionmentioning
confidence: 99%
“…Addition of exogenous antioxidants during the development of bovine embryos is important to provide hyper-thermo resistance to overcome the negative effects (Rynkowska, 2011), which increase the chance of embryos, even those of fair quality, to develop to blastocysts. Supplementations of antioxidants at optimal levels have been demonstrated to have a positive effect on embryo development (Ara Ahmed et al, 2016). In this respect, melatonin administration to heat-stressed mice alleviated hyperthermia-induced early embryonic death (Matsuzuka et al, 2005).…”
Section: Effect Of Interactionmentioning
confidence: 99%